1999
DOI: 10.1029/1998jd200056
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of climate and past atmospheric circulation patterns from central West Antarctic glaciochemistry

Abstract: changes over distances of 50-100 km and sea-salt concentrations drop by 50% between the middle two sites. One likely contributor to the high variability seen at this spatial scale is variability in synoptic-and finer-scale meteorology. Empirical orthogonal function (EOF) analysis shows that 80% or more of the variance in site chemistry can be attributed to two types of air masses: winter season air (50-70% of site variance) with a strong marine signature (heavy loading of sea-salt species) and summer season ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…The drill locations are at 82°22 0 01 00 S, 119°16 0 59 00 W (920 masl) and at 82°05 0 38 00 S, 115°13 0 41 00 W (1315 masl). In the literature the cores are also known as Central West Antarctica A, CWA-A and CWA-B [10]. The two drill sites are within a few hundred km of the WAIS Divide site and show average annual snow accumulation rates (over the past 40 yr) of 13.9 cm weq yr À1 at BSH-2 and 22.5 cm weq yr À1 at BSH-5, similar to the snow accumulation rate of $20 cm weq yr À1 at WAIS Divide.…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The drill locations are at 82°22 0 01 00 S, 119°16 0 59 00 W (920 masl) and at 82°05 0 38 00 S, 115°13 0 41 00 W (1315 masl). In the literature the cores are also known as Central West Antarctica A, CWA-A and CWA-B [10]. The two drill sites are within a few hundred km of the WAIS Divide site and show average annual snow accumulation rates (over the past 40 yr) of 13.9 cm weq yr À1 at BSH-2 and 22.5 cm weq yr À1 at BSH-5, similar to the snow accumulation rate of $20 cm weq yr À1 at WAIS Divide.…”
Section: Samplesmentioning
confidence: 99%
“…For radionuclide analysis we used core pieces of 20-30 cm length, corresponding to age intervals of $1.5 yr for BSH-2 and $0.8 yr for BSH-5. Each laboratory cut their own cores into four sections, so there is a slight offset (<6 cm) between the individual samples, but the four samples of each core combined should yield the same 10 The typical sample size is $1 kg, ranging from 0.7-1.3 kg for individual samples.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that this variability has an approximately 21 year period, the authors speculate that it is linked with the 22 year solar Hale cycle. Reusch et al (1999) have analysed and interpreted a series of 4 short (approximately 40 years of accumulation) ice cores from near Byrd station, west Antarctica, that were separated by only 200km in total. Whilst this multisite technique represents an interesting methodological advance, the circulation reconstruction presented in this work was basic: they identified two EOFs of note -marine sea-salt influenced winter air masses and biogenically and stratospherically influenced summer air masses.…”
Section: More Recent/advanced Reconstructionsmentioning
confidence: 99%
“…Considerable efforts have been made to reconstruct the historical SIE variations and atmospheric circulation during past decades to centuries through the Antarctic ice core records (Abram et al, 2013;Goodwin et al, 2004;Kreutz and Mayewski, 1999;Mayewski et al, 2004;Meyerson et al, 2002;Peel and Mulvaney, 1992;Reusch et al, 1999;Russell and McGregor, 2009;Souney, 2002;Vance et al, 2013;Xiao et al, 2013Xiao et al, , 2004Yan et al, 2005). The findings revealed that sea salt ions (mainly Na + and Cl  ), methanesulphonic acid (MSA) and non-sea salt sulfate (nss-SO 4 2 ) were good indicators of the SIE (Abram et al, 2013;Meyerson et al, 2002;Xiao et al, 2013) and associated atmospheric circulation patterns, such as the Southern Oscillation Index (SOI) (Xiao et al, 2004), Southern Annular Mode (SAM) (Xiao et al, 2013), ENSO (Abram et al, 2013;Vance et al, 2013), and Pacific Decadal Oscillation (PDO) (Vance et al, 2013).…”
mentioning
confidence: 99%